Aspects of Religious Life at Ancient Mari as Seen through a Study of Archives Royales de Mari 21 - Beyer, Bryan E. (1985)
Ph.D. Dissertation; Jewish Institute of Religion (Ohio); Co-Referees: D. B. Weisberg, S. Greengus. - Order No. DA8517071; cf. Diss Abstr 46/6 (1985) 1711-A.